Strategic planning of pt pertamina gas to anticipate governmet initiatives - Saniya, Hidayatus; Rudito, Priyantono (The Indonesian Journal of Business Administration, 2018)
Abstract – PT Pertamina Gas (Pertagas) is a gas transporter company that needs to formulate strategy to survive in the business because gas business is a government-regulated business. In addition to regulation, the trend of gas transportation business tends to decline and pressure from the competitors is getting bigger. In order to anticipate those threats, Pertagas should analyze internal and external environment business to generate strategies. Strategies formulated consist of corporate strategy, business strategy and functional strategy which can be implemented to achieved vision and mission of the company. The strategies expected to increase company’s performance and competitive advantage to anticipate environmental changes in gas industry. Keywords: Competition, Gas Business, Performance, Regulation, Strategy